PENINGKATAN KETERAMPILAN MENULIS TEKS PANTUN MELALUI TEKNIK MIND MAPPING PADA SISWA KELAS III DI SD NEGERI 006 RAMBAH KABUPATEN ROKAN HULU - Reno Marita (JURNAL PENDIDIKAN ROKANIA, 2019)
This study was conducted to obtain a description of the process of improving the skill of poetry text writing aided by mind mapping of third grade students of SDN 006 Rambah Rokan Hulu. The research method used was classroom action research conducted in two cycles. Each cycle consists of four stages of research, namely planning, implementation, observation, and reflection. The data of this study are observations about the actions of teachers and students in learning, field notes and student learning outcomes. Data from observations of teacher activities and field notes were analyzed qualitatively. Data on learning outcomes to write pantun texts and observations of student activities were analyzed quantitatively. The results showed that mind mapping used as a tool in learning can improve student learning activities and outcomes in writing pantun texts. The learning process with the help of mind mapping helps students generate key ideas and explanatory ideas, and connect these ideas in coherent and coherent sentences. Thus, learning to write poetry texts aided by mind mapping makes students think critically, logically, and systematically. Meanwhile, factors that hinder learning to write pantun texts with the help of mind mapping are less than optimal classroom management and lack of student vocabulary mastery.